Management of alemtuzumab-induced Graves’ disease in pregnancy: a case report and literature review - Teliti, Marsida; Gallo, Maria; Costa, Pietro; Chytiris, Spyridon; Magri, Flavia; Rotondi, Mario (Frontiers in Immunology, 2025)
BackgroundAlemtuzumab (ALZ), a monoclonal antibody used to treat relapsing-remitting multiple sclerosis (RRMS), is associated with a high risk of autoimmune thyroid disorders, particularly Graves’ disease (GD). Managing ALZ-induced GD during pregnancy presents unique challenges due to fluctuating thyroid function and potential fetal risks. However, the literature on this specific condition remains limited, with only a few case reports and commentaries available.Case reportThe case-history of a 36-year-old woman diagnosed with GD at 11 weeks of gestation, 16 months after receiving her last ALZ dose is described. She was treated with methimazole (MMI), with multiple dose adjustments throughout pregnancy to maintain euthyroidism. Despite persistently elevated TSH receptor antibodies levels, fetal development occurred normally, and she delivered a healthy newborn. The infant experienced transient neonatal hyperthyroidism with spontaneous recovery without treatment. In the postpartum period, both mother and child were closely monitored. As the infant’s condition stabilized, the mother’s MMI dose was gradually increased. At seven months postpartum, she remains euthyroid on 15 mg/day of MMI, with no clinical/radiological signs of multiple sclerosis relapse.ConclusionThe present case adds to the limited literature on ALZ-induced GD in pregnancy, providing further insight into the variability of disease onset, progression, and neonatal outcomes. It underscores the importance of close monitoring and a multidisciplinary approach to ensure optimal maternal and fetal health.